2005
DOI: 10.1007/s00330-005-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Kyphosis reduction and the rate of cement leaks after vertebroplasty of intravertebral clefts

Abstract: To assess the results of vertebroplasty in patients with intravertebral clefts compared to patients with normal osteoporotic fractures, we evaluated the pre- and postoperative images and pain scores (VAS) of 114 patients with 192 vertebroplasty procedures treated between March 2002 and February 2005. Intravertebral clefts were identified on conventional radiographs, MR or CT images as gas- or fluid-filled spaces adjacent to an endplate of a fractured vertebra. Forty-four vertebrae showed intravertebral clefts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 26 publications
6
66
0
1
Order By: Relevance
“…Ha et al 45 found the difference between patients with and without a cleft in the Oswertry Disability Index (ODI) and visual analog scale (VAS) scores at the final follow-up was not statistically significant. This agrees with the results of McKiernan et al 29 Krauss et al 46 also found pain reduction to be the same in both groups, but patients with intravertebral clefts showed a significant reduction of the kyphosis angle compared to noncleft patients during vertebroplasty.…”
Section: Treatmentsupporting
confidence: 90%
See 3 more Smart Citations
“…Ha et al 45 found the difference between patients with and without a cleft in the Oswertry Disability Index (ODI) and visual analog scale (VAS) scores at the final follow-up was not statistically significant. This agrees with the results of McKiernan et al 29 Krauss et al 46 also found pain reduction to be the same in both groups, but patients with intravertebral clefts showed a significant reduction of the kyphosis angle compared to noncleft patients during vertebroplasty.…”
Section: Treatmentsupporting
confidence: 90%
“…This higher rate, compared to that of compression fractures without intravertebral vacuum clefts, may be attributed to the presence of a cleft. However, Krauss et al 46 Cement leakage types differed in osteoporotic compression fractures with and without intravertebral vacuum clefts. Jung et al 13 reported that the leakage types were intradiscal (65.0%), perivertebral venous (25%), epidural (5%), and foraminal (5%) in compression fractures with clefts; and epidural (44.0%), perivertebral venous (32%), and intradiscal (24%) in those without clefts.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertebroplasty for vertebral fracture with or without intravertebral clefts have yielded similar results in terms of pain relief [12,13]. The results with regard to kyphosis reduction, maintenance of disc height and risk of complications, such as cement extrusion after vertebroplasty, for fractures with or without clefts, however, have been heterogeneous [12,13].…”
Section: Diagnostic Imagingmentioning
confidence: 99%